European Union regulations on algorithmic decision-making and a "right to explanation" - Goodman, B; Flaxman, S (Association for the Advancement of Artificial Intelligence, 2017)
We summarize the potential impact that the European Union’s new General Data Protection Regulation will have on the routine use of machine learning algorithms. Slated to take effect as law across the EU in 2018, it will place restrictions on automated individual decision-making (that is, algorithms that make decisions based on user-level predictors) which ‘‘significantly affect’’ users. When put into practice, the law may also effectively create a ‘‘right to explanation,’’ whereby a user can ask for an explanation of an algorithmic decision that significantly affects them. We argue that while this law may pose large challenges for industry, it highlights opportunities for computer scientists to take the lead in designing algorithms and evaluation frameworks which avoid discrimination and enable explanation.